ANALISIS SOSIAL EKONOMI USAHATANI KONSERVASI PADA LAHAN MIRING DENGAN POLATANAM JAMBU METE, KEMIRI, MELINJO DAN JATI DI KABUPATEN LOMBOK BARAT - JT. Yuhono; Sintha Suhirman (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
Sosio-economic analyses of conservation farming on sloping land by planting pattern of cashew, candlenut, Gnetum gnemon and teak at West Lombok DistrictThe socio-economic analyses was con-ducted on research activity of conservation planting pattern of estate and forestry crops on sloping land at West Lombok district in the planting season 2001. The area on farm research (OFR) was selected by purposive method on 8 - 30° sloping land onspread out area 10 ha.  This study aimed to analyses the socio-economic aspects of conservation far-ming on sloping land by planting pattern of estate and forestry crops. The aspect that adoption ability of farming technology mana-gement and its income of conservation far-ming neither individuality nor farmer group. This research involved 20 cooperative far-mers that devided into 10 farmers that wor-king by individuality @ 0.50 ha per farmer and 10 farmers that working by group (5 ha). Data of farming system and problems of technical and social were collected from coo-perative farmer. Data were analysed by des-criptive and enterprise methods. From this the preliminary study was received a conclusion that many of sloping land was not optimaly used yet by planting pattern of estate and forestry crops at West Sekotong village. In generally, farming pattern still subsisten, and they are not yet known the conservation farming technology on sloping land. Establi-shment of farmer group by extension emplo-yee appear still not good socialized yet. The respons of cooperative farmer on the techno-logy of conservation farming is high enough that shown by actively partipation of farmer during following a discussion or training and implimentation of research activity in the field. The net income of farmers that working by group were higher than farmers that working by individuality. (Rp. 1,674,000,- versus    Rp. 1,348, 000,- per  0.50 ha).